Derajat Otonomi Fiskal Daerah Kabupaten Bangka Barat - Pebri Harto; Intiyas Utami; Rulyanti Susi Wardhani (Politeknik Ganesha Medan, 2022)
This study aims to determine and analyze the Degree of Autonomy/Fiscal Independence in West Bangka Regency and analyze how big the correlation between GRDP and PAD is in West Bangka Regency. This study uses a quantitative approach with data analysis methods and hypothesis testing using panel data regression analysis. The data used in this research is the Regional Finance data of West Bangka Regency and the GRDP of West Bangka Regency in 2011 - 2020. The results of the study show that the value of the Degree of Fiscal Autonomy (DOF) of West Bangka Regency in the period 2011 to 2020 with the category